Peranan Financial Controller Dalam Membantu Manajemen Mengefektifkan Pengendalian Terhadap Transaksi Penjualan Cabang Pada PT Cahaya Sakti Multi Intraco - ., Sudarsono; ., Iriyadi (Institut Bisnis dan Informatika Kesatuan, 2016)
Many companies expand by way of example that is opening new branches in various cities to facilitate marketing. With so many branches owned by the company, there is increasing demand to consider control over all aspects of the sales including control aspects. Sales transaction is one of the financial transactions in the branch office that needs special attention. This is due to the sales will get optimal profit only if supported by the applicable criteria or requirements of the company. Based on the descriptions, the purpose of this study was to determine how the role of Financial Controller in helping to streamline the management controls over sales transactions of branch offices.The results showed that the role of Financial Controller in Bogor branch office of PT.Cahaya Sakti Multi Intraco greatly help them oversee the financial transactions the Branch office did to support the achievement of sales targets, and conduct overall control on branch office. Financial Controller provides useful reports for management in the form of Performance Reports of Branch office as a whole containing informations about the effectiveness and/or ineffectiveness of operating Branch. Control sales in Bogor Branch office is considered to be effective. This is evident from the sales restraint heavily influenced by the role of the Financial Controller in overseeing the sales transactions and provide data and information relating to sales, thus sales can be controlled and run in accordance with the applicable criteria.